A PRODUCTIVE LEARNING ENVIRONMENT: A BRIEF OVERVIEW - Muhammad fauzan ansyari (Al-Manar : English and Arabic Journal, 2014)
This article presents a review that provides insight in the concept, characteristics, people involved, and purposes of a productive learning environment (PLE). As is expected, teaching and learning in a productive learning environment results in a student-centered learning, higher academic performance, and improvement of students’ intrinsic motivation. Based upon review on research and non-research papers as well as books, results show that 1) goal-oriented learning, authentic and reality-based learning, motivating and engaging activities, active and supportive knowledge construction, self-regulated, and reflective are the components that characterize a PLE, 2) a PLE should be promoted collectively, and 3) a PLE is intended to improve both process and outcome of learning.